2000
DOI: 10.1042/0264-6021:3450121
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the rat pancreatic bile-salt-dependent lipase by casein kinase II is essential for secretion

Abstract: Bile-salt-dependent lipase (BSDL, EC 3.1.1.-) is an enzyme expressed by the pancreatic acinar cells and secreted as a component of the pancreatic juice of all examined species. During its secretion route BSDL is associated with intracellular membranes. This association allows the complete glycosylation of the enzyme or participates in the inhibition of the enzyme activity, which can deleterious for the acinar pancreatic cell. Thereafter, the human BSDL is phosphorylated by a serine/threonine protein kinase and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 48 publications
2
18
0
Order By: Relevance
“…Moreover, O-glycosylation could be important for the solubility of the protein, protecting against self-association caused by exposed hydrophobic surfaces on the globular core of the enzyme (17). In the trans-Golgi area, phosphorylation releases CEL from the multiprotein folding complex, and the protein is concentrated and stored in zymogen granules before its secretion to the cell exterior upon stimulation (18).…”
mentioning
confidence: 99%
“…Moreover, O-glycosylation could be important for the solubility of the protein, protecting against self-association caused by exposed hydrophobic surfaces on the globular core of the enzyme (17). In the trans-Golgi area, phosphorylation releases CEL from the multiprotein folding complex, and the protein is concentrated and stored in zymogen granules before its secretion to the cell exterior upon stimulation (18).…”
mentioning
confidence: 99%
“…Altogether, these results suggested that the dissociation of secretioncompetent molecules of BSDL from the folding complex occurs after the trans-Golgi compartment, probably in the transGolgi network, which is already known to segregate vesicle populations in cells [48]. However, the phosphorylation of BSDL and its release from intracellular membranes does not signify that all BSDL molecules dissociate from Grp94 [36], and two populations of BSDL seem to be secreted in the pancreatic juice [14]. The first population consists of monomeric BSDL, while the second population consists of BSDL complexed to Grp94.…”
Section: Discussionmentioning
confidence: 76%
“…from the folding complex) after phosphorylation of the enzyme [35]. This phosphorylation occurs within a genistein-sensitive compartment of AR4-2J cells [36]. Because genistein inhibits the formation and the release of cargo vesicles in the trans-Golgi network [47] one may suspect that the BSDL dissociates from the membrane folding complex in this latter compartment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This Grp 94 controls the late folding steps and the sorting of the active enzyme toward secretion (8). Once in the trans-Golgi network and after completion of glycosylation (9,10), the complex is released from membranes on the phosphorylation of the threonine residue at position 340 (11) by a protein kinase CKII (12,13). Once released from intracellular membranes, BSDL enters into the secretion route until the duodenum where it accomplishes its physiologic role.…”
Section: Introductionmentioning
confidence: 99%